Antibacterial effect of 3D printed mesoporous bioactive glass scaffolds doped with metallic silver nanoparticles. (1st January 2023) - Sánchez-Salcedo, Sandra; García, Ana; González-Jiménez, Adela; Vallet-Regí, María
Abstract: The development of new biomaterials for bone tissue regeneration with high bioactivity abilities and antibacterial properties is being intensively investigated. We have synthesized nanocomposites formed by mesoporous bioactive glasses (MBGs) in the ternary SiO2, CaO and P2 O5 system doped with metallic silver nanoparticles (AgNPs) that were homogenously embedded in the MBG matrices. Ag/MBG nanocomposites have been directly synthesized and silver species were spontaneously reduced to metallic AgNPs by high temperatures (700 °C) obtained of last MBG synthesis step. Three-dimensional silver-containing mesoporous bioactive glass scaffolds were fabricated showing uniformly interconnected ultrapores, macropores and mesopores. The manufacture method consisted of a combination of a single-step sol–gel route in the mesostructure directing agent (P123) presence and a biomacromolecular polymer such as (hydroxypropyl)methyl cellulose (HPMC) as the macrostructure template, followed by rapid prototyping (RP) technique. Biological properties of Ag/MBG nanocomposites were evaluated by MC3T3-E1 preosteoblastic cells culture tests and bacterial ( E. coli and S. aureus ) assays. The results showed that the MC3T3-E1 cells morphology was not affected while preosteoblastic proliferation decreased when the presence of silver increased. Antimicrobial assays indicated that bacterial growth inhibition and biofilm destruction were directly proportional to the increased presence of AgNPs in the MBG matrices. Furthermore, in vitro co-culture of MC3T3-E1 cells and S. aureus bacteria confirmed that AgNPs presence was necessary for antibacterial activity, and AgNPs slightly affected cell proliferation parameters. Therefore, 3D printed scaffolds with hierarchical pore structure and high antimicrobial capacity have potential applications in bone tissue regeneration. Statement of significance: This study combines three key scientific aspects for bone tissue engineering: (i) materials with high bioactivity to repair and regenerate bone tissue that (ii) contain antibacterial agents to reduce the infection risk (iii) in the form of three-dimensional scaffolds with hierarchical porosity. Innovative methodology is described here: sol-gel method, which is employed to obtain mesoporous bioactive glass matrices doped with metallic silver nanoparticles where different polymer templates facilitate the different size scales presence, and rapid prototyping technique that provides ultra-large macroporosity according to computer-aided design. The dual scaffolds obtained are biocompatible and deliver active doses of silver capable of combating bone infections, which represent one of the most serious complications associated to surgical treatments of bone diseases and fractures. Graphical abstract: Image, graphical abstract